Pemekaran Daerah dan Implikasinya Pada Pembangunan - Adies Saputra (Jurnal Administrasi Publik, 2008)
Regional autonomy open the possibility of uncontrolled regions' extension which may cause conflicts which at the end may become a constraint to fulfill the aims of regional development. We cannot stop the extension. Nonetheless the above problems can be prevented by policies which accommodate the interest of all parties.Keywords: regional autonomy, development, region's extension